Role of antioxidants in amelioration of radiation-induced suppression of delayed hypersensitivity to oxazolone - Soha Mahmoud Hussien Farahat; Abdelgawad Mohammed Hashem; Mahmoud Hassan Shabon (Cairo : Soha Mahmoud Hussien Farahat, 2015)
The main purpose of the present study was to assess the role of antioxidants supplementation in gamma radiation- induced impact on delayed type hypersensitivity (DTH) response to oxazolone in Swiss albino mice. Sixteen groups of Swiss albino, each of ten, have been used in this study. Eight groups have exploited to assess the effect gamma radiation, antioxidant dry extracts alone or together with total body irradiation with 2 Gy of Gamma irradiation on the induction of DTH and eight other groups have been utilized to evaluate the effect of gamma radiation, antioxidant dry extracts alone or combined with gamma rays exposure on the elicitation of DTH. In each of the eight groups, one served as a control, the second received 2 Gy gamma irradiation 24 hr before the induction and the elicitation of mouse ear swelling test to 1% oxazolone. Six groups were maintained on oral supplementation of green tea (GTE), grape seed (GSE) and echinacea purpurea (EP) extracts via drinking water, alone or together with total body irradiation with 2 Gy of Gamma radiation
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: Antioxidants; Delayed type hypersensitivity; Gamma radiation